Revision of the longiusculus-group of the genus Hydroporus Clairville, 1806 (Coleoptera: Dytiscidae) - Shaverdo, Helena V. (Zootaxa, 2006)
The taxonomic position and synonymy of Hydroporus longiusculus Gemminger and Harold and H. pervicinus Fall are discussed and re-descriptions are provided. Hydroporus hirtellus LeConte syn.n., H. perplexus Sharp syn.n., and H. utahensis Gordon syn.n. are found to be junior synonyms of H. longiusculus. Hydroporus hirsutus Gordon syn.n. and H. similaris Fall syn.n. are found to be junior synonyms of H. pervicinus. Both species are the only members of the longiusculus-group. Hydroporus simplex Gordon, previously attributed to the longiusculus-group, is transferred to the nigellus-group. A lectotype is designated for H. perplexus Sharp. The location of the primary types of H. longiusculus remains unknown. Morphological variability of H. longiusculus and H. pervicinus is discussed and illustrated. Geographical distributions of these two species are mapped and some notes on their ecology are presented. Based on extreme morphological similarity to H. tenebrosus LeConte, H. subpubescens LeConte is transferred to the nigellus-group; thus, the subpubescens-group is omitted.